Interface and dielectric properties of Al/p-Si diode by organic composite interlayer for MOS - Demirezen, S.; Dere, A.; Cetinkaya, H. G.; Mansour, Shehab A.; Yakuphanoğlu, Fahrettin (Springer, 2025)
Thin films with different ratios (0, 0.5, and 2 wt%) of GO-doped P3HT:PCBM were synthesized on p-Si wafers using the spin coating technique to create Al/GO:P3HT:PCBM/p-Si structures. In order to comprehensively investigate the effect of GO doping on P3HT:PCBM in terms of AC electrical conductivity (sigma ac), complex permittivity (epsilon*), complex electric modulus (M*), and complex impedance (Z*), we have performed capacitance/conductance-voltage (C/G-V) measurements on Al/GO:P3HT:PCBM/p-Si structures over a wide range of frequencies and voltages. Different ratios (0, 0.5, and 2 wt%) of GO in P3HT:PCBM layers were deposited on a p-type Si wafer as an interlayer. The values of the complex dielectric constant/loss (epsilon(y)/epsilon ''), the loss tangent (tan delta), the AC electrical conductivity (sigma ac), and the real/imaginary components of the complex electric modulus (M-y, M '') were determined from the C/G-V measurements as a function of frequency, ranging from 0.5 to 2.5 V with 100 mV steps. All parameters showed distinct frequency/voltage dependencies, surface/dipole polarizations, and interlayer effects, especially at low and intermediate frequencies. In particular, the elevated dielectric constants measured (approximately 52 for 0.5% GO concentration and 60 for 2% GO concentration) at frequencies as high as 10 kHz indicate that GO:P3HT thin films are a viable alternative to conventional SiO2 dielectrics. The real component of the dielectric permittivity maintained at 10 kHz exceeds that of conventional SiO2 insulators (3.8) by a factor of 16, demonstrating the superior charge storage capacity of these composite films and their potential to replace standard insulators in energy storage applications. Furthermore, the value of sigma ac increased with increasing doping rate of GO, indicating potential advantages of using high-dielectric organic thin films between metal and semiconductor instead of conventional metal/oxide/semiconductor (MOS) structures. The plot of ln(sigma(aa)) as a function of ln(f) for the synthesized structures reveals two distinct linear regions, each characterized by varying slopes. This finding indicates the presence of two independent conduction mechanisms operating within the structures at ambient temperature. Moreover, the M '' exhibits a significant peak, the location of which advances toward higher frequencies as the applied voltage increases. This peak phenomenon can be ascribed to a diminution in polarization effects alongside contributions arising from interfacial or surface states.
Keywords: Ac Electrical-Conductivity; Frequency; Impedance; Modulus; Spectroscopy; Relaxation; Behavior; Voltage; Layer; Oxide